A novel study on laser lap welding of refractory alloy 50Mo–50Re of small-scale thin sheet. (February 2017) - Liu, Peng; Feng, Ke-yun; Zhang, Ge-ming
Abstract: The refractory alloy 50Mo–50Re thin sheet was welded successfully by small-scale laser lap welding. There were obvious gas pores and cracks near the interface of the laser lap-welded joint. The hardness (HV420) near the interface zone of laser lap-welded joint was obviously higher than that in the heat-affected zone (HV370) and base metal (HV290). The fracture morphology near the interface zone shows the typical brittle intergranular fracture. The presence of some compounds with elements Mo, Re, and O was also observed in the grain and its boundary along the fracture. The presence of some possible brittle coarse structure and hazardous elements near the interface zone of joint could be the key factor in producing the high hardness and the intergranular fracture of joints. Highlights: The refractory 50Mo–50Re alloy was welded successfully by laser lap welding. The microstructure and fracture characteristic were tested and analyzed. The effect factor of gas pores and cracks formed were discussed.